2019
DOI: 10.3390/md17010041
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Cured Glycol Chitosan Hydrogel for Ovarian Cancer Drug Delivery

Abstract: In this study, we prepared an injectable drug delivery depot system based on a visible light-cured glycol chitosan (GC) hydrogel containing paclitaxel (PTX)-complexed beta-cyclodextrin (β-CD) (GC/CD/PTX) for ovarian cancer (OC) therapy using a tumor-bearing mouse model. The hydrogel depot system had a 23.8 Pa of storage modulus at 100 rad/s after visible light irradiation for 10 s. In addition, GC was swollen as a function of time. However, GC had no degradation with the time change. Eventually, the swollen GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 28 publications
0
52
0
Order By: Relevance
“…The methacrylic group was conjugated to GC for photo-curing [10][11][12]. GC (0.003 mmol, 1.5 g) was dissolved in water (500 mL).…”
Section: Preparation Of Doxorubicin·hydrochloride (Dox·hcl) And/or Hpmentioning
confidence: 99%
See 2 more Smart Citations
“…The methacrylic group was conjugated to GC for photo-curing [10][11][12]. GC (0.003 mmol, 1.5 g) was dissolved in water (500 mL).…”
Section: Preparation Of Doxorubicin·hydrochloride (Dox·hcl) And/or Hpmentioning
confidence: 99%
“…Although systemic drug-delivery systems are efficient, their therapeutic applications are sometimes limited by complicated preparation. Hydrogel-medicated local drug delivery systems are capable of directly delivering anticancer drugs to targeted sites without complicated procedures because they can be implanted near cancer tissues [10][11][12]. We have already reported that a visible light-cured injectable glycol chitosan (GC) hydrogel-based local drug-delivery system can be used as an anticancer drug carrier for treatment of several solid cancers [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are some water‐soluble systems for delivering PTX, including TAXOL® and Genexol® PM Injection, they are not the best options because of the lack of proper targeting and usage of a toxic excipient. In addition, other drug delivery systems, such as using nanomaterials and microspheres, which are based on the polymer or lipid, are also not effective due to fast clearance, frequent dosing, insufficient penetration into the tumor, and short half‐life . In order to solve these problems, Hyun et al used a delivery system in which light‐cured glycol chitosan hydrogel, including PTX‐complexed beta‐cyclodextrin (β‐CD), was used.…”
Section: Chitosan Functions As a Delivery Agent For Chemotherapeutic mentioning
confidence: 99%
“…In addition, other drug delivery systems, such as using nanomaterials and microspheres, which are based on the polymer or lipid, are also not effective due to fast clearance, frequent dosing, insufficient penetration into the tumor, and short half‐life . In order to solve these problems, Hyun et al used a delivery system in which light‐cured glycol chitosan hydrogel, including PTX‐complexed beta‐cyclodextrin (β‐CD), was used. CP is another chemotherapy drug used in ovarian cancer, although there are multiple problems in using this drug, such as its poor solubility in both water and oil phases, high toxicity in healthy tissues caused in its administration intravenously, and rapid clearance caused by its low molecular weight in intravenous administration .…”
Section: Chitosan Functions As a Delivery Agent For Chemotherapeutic mentioning
confidence: 99%